Woman and Political Communication: Megawati dan Pemimpin Simbolik - Dini Safitri (Jurnal Komunikasi, 2014)
The involvement of women in politics in Indonesia has fundamental problems, namely the minimal representation of women in public spaces. This is because women have been stigmatized and are positioned in the domestic sphere, taking care of household problems, without being able to develop themselves in the public sphere. In fact, there are already rules about the 30% quota for women in parliament, but has not yet been realized. When you glance at the historical record and the women's movement toward public spaces, has existed since Indonesia's independence in 1945. Rights of women to choose is basically recognized. However, the position of women in politics, very volatile in Indonesia. It is because the democratic process in Indonesia not through means gradual (gradual) but through jumps (leaps). Each leap democracy will produce political visions different countries and sometimes very dramatic in seeing women's issues. This phenomenon, then bring up the figure of Megawati's Indonesian women representing the highest ever reached peak Indonesian leader. As a leader, Megawati is the symbolic leader. Megawati is symbolic leader who tried to communicate how to obtain the status, prestige and reputation, or in other words, to fulfill the functions and symbols are fused.